Sudden cardiac death in young athletes: time for a Nordic approach in screening? - Hernelahti, M.; Heinonen, O. J.; Karjalainen, O.; Nylander, E.; Börjesson, M. (Scandinavian Journal of Medicine & Science in Sports, 2008)
In 2005, the European Society of Cardiology published recommendations for cardiovascular screening in athletes. Discussion on whether screening is beneficial is ongoing. Recently, the first prospective results on effectiveness of screening in preventing sudden deaths were published from Italy. The results were supportive of screening, but did not provide conclusive evidence. Our suggestion for a Nordic approach on this issue is a directed cardiovascular examination initially involving elite athletes, because this is feasible with respect to the Nordic health care systems and the organization and logistics of elite competitive sports, but also because of the negative aspects of screening large populations. This directed cardiovascular examination would include personal and family history, clinical examination, and electrocardiography (ECG). Further examinations should thereafter be carried out in athletes with suggestive findings in the initial evaluation. The directed cardiovascular examination should be voluntary. It should be conducted at least once, with information on alarming symptoms (syncope, chest pain or dizziness during exercise) and heredity (sudden cardiac death or hereditary heart disease in near relatives) stressed to the athlete as indications for necessary check-ups in the future. The examination would also provide the athlete with an ECG recording, which is valuable as a reference at a later time.